“La Constitución de los Pueblos de Occidente”. Une proposition inédite du voyageur cAlî Bey l’Abbasside pour le Maroc dans l´Arxiu Històric de la Ciutat de Barcelona (AHCB, Col. Toda, Ms B.162-II) - Mercè Viladrich (Université de Provence, 2006)
The aim of this paper is to introduce and edit the text Constitution of the people of Occident written by the Catalan traveller Domènec Badía i Leblich (1767-1818), known under the name of cAlî Bey the Abbassi. This big Charter was intended to be accepted as lawful text in the Empire of Morocco. Civil servant at the service of the prime minister of Carlos IV, Manuel de Godoy, Domènec Badía travelled in 1803 in Morocco, in the Arabic peninsula and the Middle East and gained a certain notoriety among his contemporaries by telling his adventures in a book called Trips of Ali Bey in Asia and in Africa, a work which blends historical truth and invention and in which the author reveals a pathological psychology.